2020
DOI: 10.1101/2020.04.21.053272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal complexity is attenuated in chronic migraine and restored by HDAC6 inhibition

Abstract: Migraine is the third most prevalent disease worldwide and current therapies provide only partial relief. Greater insight into molecular migraine mechanisms would create novel therapies. Cytoskeletal flexibility is fundamental to neuronal-plasticity and is dependent on microtubule dynamicity. Histone-deacetylase-6 (HDAC6) decreases microtubule dynamics by deacetylating its primary substrate, α-tubulin. We use validated models of chronic migraine to show that HDAC6-inhibition is an effective migraine treatment … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 84 publications
4
12
1
Order By: Relevance
“…This study, and previous work, 15 showed decreased neuronal complexity within the vlPAG following chronic migraine and CSD. We determined if CRPS produced similar changes in this key pain processing region (Figure 5A).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…This study, and previous work, 15 showed decreased neuronal complexity within the vlPAG following chronic migraine and CSD. We determined if CRPS produced similar changes in this key pain processing region (Figure 5A).…”
Section: Resultssupporting
confidence: 87%
“…The aim of this study was to further investigate alterations that occur following chronic migraine and assess if similar alterations in cytoarchitecture are observed in a hind paw model of CRPS. We previously showed that there were neuronal cytoarchitectural differences in key migraine pain processing regions following the NTG model of chronic migraine 15 . These results revealed a novel mechanism responsible for the transition of migraine from an episodic to a chronic condition.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Stellate neurons also consist of three groups (4042), while basket neurons are from (43) and (44). Finally, pyramidal neurons are totally taken from four groups (4548). The number of points that make up a neuron varies from 1 × 10 3 to 6 ×10 3 .…”
Section: Methodsmentioning
confidence: 99%